Expression of Connexin 43 in Synovial Tissue of Patients With Rheumatoid Arthritis - Tomohiro MATSUKI; Yuji ARAI; Shinji TSUCHIDA; Ryu TERAUCHI; Ryo ODA; Hiroyoshi FUJIWARA; Osam MAZDA; Toshikazu KUBO (Archives of Rheumatology, 2016)
Objectives: This study aims to identify the distribution and expression level of connexin 43 (Cx43) in synovial tissue in patients with rheumatoid arthritis (RA). Patients and methods: The expression of Cx43 in synovial tissue from eight patients with RA (2 males, 6 females; mean age 59.5±2.7 years; range 52 to 71 years), five patients with osteoarthritis (2 males, 3 females; mean age 68.4±2.7 years; range 61 to 81 years), and one normal female subject (mean age 61 year) was analyzed by quantitative reverse transcriptase polymerase chain reaction and immunohistochemistry of tissue sections. Induction of Cx43 following stimulation of human RA synovial fibroblasts with tumor necrosis factor-alpha (TNF-a) cultures was examined by quantitative reverse transcriptase polymerase chain reaction. The effect of small interfering ribonucleic acid targeting Cx43 (siCx43) on the expression of TNF-a and interleukin-6 was examined using quantitative reverse transcriptase polymerase chain reaction and enzyme-linked immunosorbent assays. Results: Connexin 43 was highly expressed in RA synovial tissue, which also expressed TNF-a, but was expressed lower in osteoarthritis and normal synovial tissue. Expression of Cx43 was markedly up-regulated in RA synovial fibroblasts after stimulation with TNF-a. The over-expression of pro- inflammatory cytokines was suppressed by transfection of siCx43. Conclusion: This study shows that Cx43 is expressed in RA synovial tissue and that its expression is induced by stimulation with TNF-a. The expression of the pro-inflammatory cytokines was inhibited by transfection of siCx43. Cx43 may be a novel marker of inflammation in RA synovial tissue.